New species of Plectropsyche Ross 1947 (Trichoptera: Hydropsychidae: Hydropsychinae) - Bueno-Soria, Joaquín; Barba-Alvarez, Rafael (Zootaxa, 2015)
Two new species from Mexico and Central America of the genus Plectropsyche Ross are described and the male and female genitalia are figured. The only extant previous described species, Plectropsyche hoogstraali Ross and its synonym Plectropsyche pitella (Denning) from Mexico are studied. A map with the distribution of all known Plectropsyche species is presented and an illustrated key for the males of the extant species are included.